Multifunctional Fe3O4-Au Nanoparticles for the MRI Diagnosis and Potential Treatment of Liver Cancer - Kozenkova, Elena; Levada, Kateryna; Efremova, Maria V; Omelyanchik, Alexander; Nalench, Yulia A; Garanina, Anastasiia S; Pshenichnikov, Stanislav; Zhukov, Dmitry G; Lunov, Oleg; Lunova, Mariia; Kozenkov, Ivan; Innocenti, Claudia; et al. (Nanomaterials (Basel, Switzerland), 2020)
Heterodimeric nanoparticles comprising materials with different functionalities are of great interest for fundamental research and biomedical/industrial applications. In this work, Fe3O4-Au nano-heterostructures were synthesized by a one-step thermal decomposition method. The hybrid nanoparticles comprise a highly crystalline 12 nm magnetite octahedron decorated with a single noble metal sphere of 6 nm diameter. Detailed analysis of the nanoparticles was performed by UV-visible spectroscopy, magnetometry, calorimetry and relaxometry studies. The cytotoxic effect of the nanoparticles in the human hepatic cell line Huh7 and PLC/PRF/5-Alexander was also assessed. These Fe3O4-Au bifunctional nanoparticles showed no significant cytotoxicity in these two cell lines. The nanoparticles showed a good theranostic potential for liver cancer treatment, since the r2 relaxivity (166.5 mM-1·s-1 and 99.5 mM-1·s-1 in water and HepG2 cells, respectively) is higher than the corresponding values for commercial T2 contrast agents and the Specific Absorption Rate (SAR) value obtained (227 W/gFe) is enough to make them suitable as heat mediators for Magnetic Fluid Hyperthermia. The gold counterpart can further allow the conjugation with different biomolecules and the optical sensing.
Keywords: magnetic-plasmonic nanoparticles; nano-heterostructures; liver cancer; theranostic; MRI contrast agent